PENGARUH BUDAYA ORGANISASI DAN MOTIVASI KERJA TERHADAP KOMITMEN ORGANISASIONAL PADA PT. BANK CENTRAL ASIA, TBK. KANTOR CABANG UTAMA TANGERANG - Sumanto Sumanto; Anik Herminingsih (Jurnal Ilmiah Manajemen dan Bisnis, 2016)
his research was conducted to test the influence of organizational culture and the workmotivation toward organizational commitment in PT. Bank Central Asia, Tbk. – Tangerang main branchoffice because in the last two years this branch has not gotten any achievement from BCA Award contest,which is used as branch’s achievement benchmark. This quantitative research is causal, using nonprobability sampling method and involves 120 permanent employees as the research samples. The dataanalysis in this research used SPSS software 22th version. Based on t-test result, partially the organizationalculture has significant influence toward organizational commitment with t as 3.740, besides partiallythe work motivation has no significant influence toward organizational commitment with tcount as 1.852.Simultaneously, organizational culture and work motivation influence significantly toward organizationalcommitment with significance value 0.000. Result of the multiple linear regression analysis shows equationY=10,057+0,870X. 1+0,444X2